2019
DOI: 10.12659/msm.916764
|View full text |Cite
|
Sign up to set email alerts
|

SF36 Is a Reliable Patient-Oriented Outcome Evaluation Tool in Surgically Treated Degenerative Cervical Myelopathy Cases: A Systematic Review and Meta-Analysis

Abstract: BackgroundDegenerative spinal disorders have adverse impacts on patients’ quality of life. Because the main objectives of any surgical intervention are to improve health-related quality of life and to reduce disability, instruments capable of measuring patient-oriented outcomes are now increasingly used. The aim of this study was to evaluate the use of the Short Form 36 Health Survey Questionnaire (SF36) for assessing patient-oriented outcomes of degenerative cervical myelopathy surgery.Material/MethodsA liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…In addition, there was a lowered HRQoL score for patients with multi-morbidity. This is in line with previous studies [ 7 , 14 , 22 - 24 ] and is only logical, given that multiple medications would be required to treat a variety of conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, there was a lowered HRQoL score for patients with multi-morbidity. This is in line with previous studies [ 7 , 14 , 22 - 24 ] and is only logical, given that multiple medications would be required to treat a variety of conditions.…”
Section: Discussionsupporting
confidence: 89%
“…It is measured with the RAND 36-Item Health Survey 1.0, adjusted for the Indian audience. This questionnaire has been shown to be effective and is widely used in both chronic conditions and general quality-of-life studies [ 21 , 24 , 26 ]. It is a generic questionnaire that measures eight concepts of health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SF-36 is a practical and widely-tested instrument for measuring health status and medical outcomes ( 26 ). SF36 was suitable for assessing the quality of life of patients with neuropathic pain ( 27 , 28 ) and was also often used to evaluate the quality of life of patients with PHN ( 24 ). The results of this study showed that patients in the H group had higher PCA, MCS scores at 1, 3, and 6 months after treatment than in the C group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both trials had greater than 90% patient follow-up at one year. Second, our chosen measure of physical function is based on a ubiquitous health-related quality of life instrument, with documented validity, reliability, and responsiveness [20,22,25]. The reliability of the SF instruments is of particular importance for our current study, as the utility of a tool for predicting fracture healing is predicated on its widespread reproducibility.…”
Section: Discussionmentioning
confidence: 99%